An anti – glaucomatous protein – based in-situ nano emulgel with considerable stability without surfactants and co-surfactants - Kaur, Harshita (My University, 2023)
Continuous vision impairment in glaucoma due to persistant death of retinal ganglions can lead to permanent blindness. Delivery of drug to particular parts of the anterior or posterior segment has been a major challenge due to various protective barriers and elimination mechanisms associated with the unique anatomical and physiological nature of the ocular system. Drug administration to the eye by conventional delivery systems results in poor ocular bioavailability
Keywords: Glaucoma; in-situ emulsion gel; Bio – environment; Amphillic protein structure; Nanoemulsion